TITLE WALIYUL AMRI ADH-DHARURI BI SYAUKAH AS NU’S SUPPORT TO SOEKARNO IN GUIDED DEMOCRACY 1959-1965 - Asa’ari, Asa’ari; Ahmad, Jafar; Nurjaman, Andri; Witro, Doli; Alghani, Raid (Balai Penelitian dan Pengembangan Agama Semarang, 2022)
The Nahdlatul Ulama Party is one of the Islamic parties that became a loyalist party to President Soekarno during the implementation of guided democracy. This is because the political strategy used by the NU Party is a realistic political strategy and tends to be accommodating and cooperative in dealing with President Soekarno’s new political situation, namely guided democracy. So that after the NU Party decided to accept guided democracy, the return of the 1945 Constitution, and the Nasakom and Manipol-Usdek, the NU party supported the leadership of President Soekarno, one of its supports was the awarding of a charter with the title waliyul amri adh-dharuri bi syaukah from Nahdlatul Ulama to President Soekarno. This paper aims to reveal the waliyul amri adh-dharuri bi syaukah title charter as moral support from the Nahdlatul Ulama Party to the leadership of President Soekarno during the guided democracy. The method used in this study is the historical method, while the approach used is the hermeneutic theory of Paul Ricoeur. The results of the study show that the waliyul amri adh-dharuri bi syaukah charter is a form of moral support from the Nahdlatul Ulama Party for the leadership of President Soekarno, so it has legitimized that the government led by President Soekarno himself is a legitimate government according to the eyes of fiqh law. This charter is also the basis for acceptance and support from the NU Party for President Soekarno and his guided democracy.